A Comprehensive Study On - How Effective Are Cyclotrons in Producing Radioisotopes for Medical Imaging Compared to Linear Accelerators or Nuclear Reactors? - Adhyayan Agarwal (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This research paper explores the foundational concepts of nuclear physics and radioactivity, examining the structure of atomic nuclei, the nature of nuclear forces, and the principles governing radioactive decay. The study covers alpha, beta, and gamma decay in detail, incorporating mathematical models to describe half-life and decay constants. A key highlight of this research is the hands-on experience gained at the Variable Energy Cyclotron Centre (VECC), where practical exposure to cyclotron operations provided unique insights into particle acceleration and isotope production. This experience enriched the theoretical understanding of high-energy nuclear reactions and their applications in medicine and industry. The paper also discusses the broader implications of nuclear science, including nuclear energy, radiation safety, and ethical concerns. By combining theoretical study with direct experimental engagement, this research offers a holistic perspective on the evolving landscape of nuclear physics and its role in shaping scientific progress.